Uso de una herramienta computacional evolutiva para el diseño y optimización de vanos residenciales en el trópico (2012)
Facades have great impact in a house´s performance being directly linked to energetic consumption and comfort. Computing sciences propose the systematization of design processes, making it possible to determine an optimal configuration for a tropical building, in order to get a desired comfort performance, based on the implementation of parametric design and artificial intelligence. This research seeks sustainable design by implementing design guidelines, geometrical parameterization and its further optimization. Now it is possible from early stages of design to provide results that can benefit people generating comfort conditions.